Upbeating Skull Vibration-Induced Nystagmus in a Case of Bilateral Sequential Superior Branch Vestibular Neuritis - Workman, Brady S.; Desmond, Alan L. (Journal of the American Academy of Audiology, 2024)
Vestibular neuritis is one of the most common reasons that someone may experience an episode of acute spontaneous vertigo, with the majority cases impacting only one ear. Cases of bilateral vestibular neuritis are rare and are thought to account for less than 10% of all cases of vestibular neuritis. Skull vibration testing is an efficient means to screen for asymmetry in vestibular function but is still in its infancy in clinical use. The ideal assessment methods and the typical patterns of skull vibration-induced nystagmus are relatively well understood; however, the presentation of skull vibration-induced nystagmus in atypical labyrinthine pathology is less clear. Skull vibration typically induces a horizontal nystagmus that beats toward the healthy labyrinth in most instances of significant labyrinthine asymmetry. We pose a case report of a patient that's symptomology and clinical test findings are most consistent with bilateral sequential superior branch vestibular neuritis with an upbeating skull vibration-induced nystagmus.
Keywords: skull vibration-induced nystagmus; vestibular neuritis; dizziness; vertigo